2006
DOI: 10.1159/000092918
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Expression of Aquaporin Water Channels in Denervated Rat Kidney

Abstract: Aims: A neural mechanism regulating aquaporin (AQP) water channels in the kidney was investigated. Methods: Male Sprague-Dawley rats were used. Renal denervation was induced by painting the renal vessels with 10% phenol. The expression of AQP1–4 proteins was determined in the denervated and contralateral kidneys. The expression was also examined in rats which were renally denervated and subjected to water restriction or deoxycorticosterone acetate (DOCA)-salt treatment. Results: Following the unilateral denerv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
11
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 27 publications
(12 reference statements)
2
11
0
Order By: Relevance
“…However, Liu et al[ 45] reported no changes in plasma levels of AVP in animals chronically treated with L -NAME in the same dose used in this study; while Zanchi et al[ 46] and Sander et al [47] reported increased activity of the sympathetic nervous system in this model of hypertension, which, according to Lee et al[ 48], should cause upregulation of AQP2 expression.…”
Section: Discussionmentioning
confidence: 53%
“…However, Liu et al[ 45] reported no changes in plasma levels of AVP in animals chronically treated with L -NAME in the same dose used in this study; while Zanchi et al[ 46] and Sander et al [47] reported increased activity of the sympathetic nervous system in this model of hypertension, which, according to Lee et al[ 48], should cause upregulation of AQP2 expression.…”
Section: Discussionmentioning
confidence: 53%
“…According to the results from experiments with denervated rat kidneys, a reduction in sympathetic nervous stimulation reduced AQP2 expression (23), and the authors suggest that renal sympathetic nerve activity may play an excitatory role in AQP2 regulation. Methylprednisolone treatment induced changes in systemic hemodynamics, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that the potential cross-talk between the two kidneys is regulated by a number of mechanistic pathways, including the renal nerves. For example, neural regulation of aquaporin in kidneys has been found following unilateral denervation, reducing the renal norepinephrine content in the contralateral kidney [10] . These changes were mediated by reduced AQP1-4 protein expression in the obstructed kidney, while an increased abundance in the contralateral kidney was observed [10] .…”
mentioning
confidence: 99%